2017
DOI: 10.1044/2016_jslhr-s-15-0071
|View full text |Cite
|
Sign up to set email alerts
|

Lipreading Ability and Its Cognitive Correlates in Typically Developing Children and Children With Specific Language Impairment

Abstract: Speech processing deficits in SLI extend also to the perception of visual speech. Lipreading performance was associated with phonological skills. Poor lipreading in children with SLI may be, thus, related to problems in phonological processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Their research also revealed that listeners with higher WM capacity were able to derive more benefit from visual information than listeners with low WM capacity when the stimuli were presented as noise. These findings are consistent with other research showing correlations between lipreading skills and WM in children (Heikkilä et al., ), hearing‐impaired adults (Andersson et al., ), and adults (Feld & Sommers, ; Lidestam, Lyxell, & Andersson, ). To date, however, studies have not investigated the relationship between lipreading skills, WM, and visual cues in L2 speech perception.…”
Section: Lipreading Skillssupporting
confidence: 92%
“…Their research also revealed that listeners with higher WM capacity were able to derive more benefit from visual information than listeners with low WM capacity when the stimuli were presented as noise. These findings are consistent with other research showing correlations between lipreading skills and WM in children (Heikkilä et al., ), hearing‐impaired adults (Andersson et al., ), and adults (Feld & Sommers, ; Lidestam, Lyxell, & Andersson, ). To date, however, studies have not investigated the relationship between lipreading skills, WM, and visual cues in L2 speech perception.…”
Section: Lipreading Skillssupporting
confidence: 92%
“…Bilingual experience also imparts advantages in a wide array of executive functions that are relevant to visual word learning and cross-modal recognition. For instance, bilingual infants and children have been found to have greater working memory retrieval than their monolingual peers (6 months-7 years: Blom, Küntay, Messer, Verhagen, & Leseman, 2014;Singh et al, 2015), a capacity that happens to be associated with greater auditory (16-20 months: Vlach & Johnson, 2013) and visual spoken word recognition in monolingual infants and children (7-14 years: Heikkilä, Lonka, Ahola, Meronen, & Tiippana, 2017;Tye-Murray, Hale, Spehar, Myerson, & Sommers, 2014). Bilingual infants and children also demonstrate (Ronquest, Levi, & Pisoni, 2010).…”
Section: Research Highlightsmentioning
confidence: 99%
“…Bilingual experience also imparts advantages in a wide array of executive functions that are relevant to visual word learning and cross‐modal recognition. For instance, bilingual infants and children have been found to have greater working memory retrieval than their monolingual peers (6 months–7 years: Blom, Küntay, Messer, Verhagen, & Leseman, 2014; Singh et al., 2015), a capacity that happens to be associated with greater auditory (16–20 months: Vlach & Johnson, 2013) and visual spoken word recognition in monolingual infants and children (7–14 years: Heikkilä, Lonka, Ahola, Meronen, & Tiippana, 2017; Tye‐Murray, Hale, Spehar, Myerson, & Sommers, 2014). Bilingual infants and children also demonstrate greater attention shifting (7 months–7 years: Byers‐Heinlein, Morin‐Lessard, & Lew‐Williams, 2017; Crivello et al., 2016) and memory generalization across contents (18–24 months: Bialystok, 2017; Brito, Sebastián‐Gallés, & Barr, 2015), two core capacities that develop along with frequent language switching and that are foundational to cross‐modal recognition.…”
Section: Introductionmentioning
confidence: 99%
“…h Lip-reading test. Word-level lipreading skills were evaluated by means of a computer-based lipreading test (Heikkilä et al, 2017). The test included 17 Finnish words presented as silent video clips in which a female speaker uttered the words.…”
Section: Training Tasksmentioning
confidence: 99%